Self affirmation and duty of memory in La Escuelita, by Alicia Partnoy (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This work focuses on the analyses of a literary testimony written by the Argentine woman writer Alicia Partnoy. The text was first published in English the United States in 1986 as The Little School and was republished in Spanish in 2006 in Argentina as La Escuelita. Relatos testimoniales. The main goal of this work is to propose an interpretation of this narration that considers on the one hand, the context of production of this text and on the other hand, its formal organization. In regard to this latter aspect, it is relevant to observe the discursive strategies, basically the characteris- tics of the enunciation (who and how narrates in the text, as well as the reasons to do it), the genres used and the tro- pes and images that allow the narrator to refer the events associated to her permanence in the clandestine center of detention and extermination called La Escuelita during the last military dictatorship in Argentina.
Keywords: Testimony; Argentine literatura; Alicia Partnoy